2006
DOI: 10.1063/1.2358926
|View full text |Cite
|
Sign up to set email alerts
|

Controlled growth of Co nanoparticle assembly on nanostructured template Al2O3∕NiAl(100)

Abstract: Based on the systematic studies of the growth temperature, deposition rate, and annealing effects, the control of Co nanoparticle density, size, and alignment is demonstrated to be feasible on a nanostructured template Al2O3∕NiAl(100). At 140–170K, a slow deposition rate (0.027ML∕min) promises both the linear alignment and the high particle density. 1.5 ML Co nanoparticle assembly sustains the density of ∼260∕104nm2 even after 800–1090K annealing. This study also indicates the possibilities of the controlled g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

3
11
0

Year Published

2007
2007
2015
2015

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 22 publications
(25 reference statements)
3
11
0
Order By: Relevance
“…As reported recently, [1][2][3][4][5][6] saturated dosing of oxygen on NiAl(100) surface at 1000-1100 K can create densely packed straight stripes of ordered Al 2 O 3 with very long length ($200 nm) and width of about 4 nm. Several different metals are found to nucleate along the boundaries between these densely packed stripes and form linear chains of monodispersed nanoparticles with size of several nanometers.…”
Section: Introductionsupporting
confidence: 54%
See 2 more Smart Citations
“…As reported recently, [1][2][3][4][5][6] saturated dosing of oxygen on NiAl(100) surface at 1000-1100 K can create densely packed straight stripes of ordered Al 2 O 3 with very long length ($200 nm) and width of about 4 nm. Several different metals are found to nucleate along the boundaries between these densely packed stripes and form linear chains of monodispersed nanoparticles with size of several nanometers.…”
Section: Introductionsupporting
confidence: 54%
“…However, other studies of similar systems 6,7,14 and, in particular, our own Auger study of the same system all indicated that metal nanoparticles grown on a thin layer of oxide will sinter slightly and then completely diffuse into the NiAl substrate below 1000 K. Thus, for reasons unknown, the oxide films in Ref. 3…”
Section: Introductionmentioning
confidence: 71%
See 1 more Smart Citation
“…The structures of these oxides have been determined by electron energy loss spectroscopy, low energy electron diffraction (LEED), scanning tunneling microscopy (STM), and low energy electron microscopy (LEEM). [11][12][13][14][15][16][17][18][19][20] Blum et al 12,13 showed that oxide stripes can form along h001i and h010i directions of the NiAl(100) surface and the stripes have a mean width of about 27 Å and a height of 3 Å or larger. Maurice et al 15 observed high resolution STM images on the oxides grown on NiAl(100) that are in agreement with the surface structure of the h-Al 2 O 3 phase.…”
Section: Introductionmentioning
confidence: 99%
“…16,17) Furthermore, because the Curie temperature of Fe particles is lower than that of Fe films, the ferromagnetic films are separated by paramagnetic nanoparticle chains at room temperature. [18][19][20] The Fe coverage range in this scenario is 2 atomic monolayers (MLs) to 10 MLs. Within this coverage range, the oxygen dosage determines the underlying alumina structure as well as the magnetic domain pattern size, which continuously decreases from larger than a micrometer at 1 L (defined as an oxygen dosage of 1.0 × 10 −6 mbar·s) to 100 nanometers at 6 L and finally disappears at 20 L, where the entire sample is covered by paramagnetic nanoparticles.…”
mentioning
confidence: 99%